Analysis the Impact of Inset Fed Design with Reference Impedance of Rectangular Microstrip Patch Antenna using Neural Network - Fariza, Nadilla; Setijadi, Eko (JAREE (Journal on Advanced Research in Electrical Engineering), 2025)
Abstract -- Research on microstrip antennas is currently growing in prevalence, as their compact design and low cost make them simple to adapt to various needs. The goal of this study is to find out how the inset-fed depth affects the impedance matching of a rectangular microstrip antenna using a simple RMSA design. The author designs the antenna to operate at a frequency of 2.4 GHz with an FR-4 epoxy substrate and simulates it using CST Suite Studio 2019 software. The research shows that adding an inset fed with a depth of 5 mm results in an impedance value of 50.28 + j3.68 Ω, which is close to the desired impedance. The computation process using Neural Network reduces simulation time by 65% faster compared to CST simulation.